DEVELOPMENT OF A PLAN TO REPAIR THE PRIORITY OF BUS TRAFFIC - Zokirov Boburjon Zoyirjon ugli; Bahodirov Giyosbek Murodjon ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article gives information about the prioritization of bus traffic is essential for sustainable urban mobility, aiming to alleviate congestion, reduce emissions, and enhance overall public transportation effectiveness. This article presents a comprehensive plan for repairing and improving the priority of bus traffic, encompassing infrastructure upgrades, policy interventions, and technological advancements. By prioritizing bus traffic, cities can create more efficient and environmentally friendly transportation systems, ultimately fostering smarter and more livable urban environments.